2017
DOI: 10.1111/imcb.1028
|View full text |Cite
|
Sign up to set email alerts
|

LncRNARP11‐714G18.1 suppresses vascular cell migration via directly targeting LRP2BP

Abstract: Atherosclerotic cardiovascular disease is considered as the leading cause of mortality and morbidity worldwide. Accumulating evidence supports an important role for long noncoding RNA (lncRNA) in the pathogenesis of atherosclerosis. Nevertheless, the role of lncRNA in atherosclerosis-associated vascular dysfunction and the underlying mechanism remain elusive. Here, using microarray analysis, we identified a novel lncRNA RP11-714G18.1 with significant reduced expression in human advanced atherosclerotic plaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
(86 reference statements)
1
17
0
1
Order By: Relevance
“…Wu et al identified lincRNA-p21 as a therapeutic target in atherosclerosis [45]. Zhan et al found that RP11-714G18.1 may play an atheroprotective role by inhibiting vascular cell migration via the RP11-714G18.1/LRP2BP/MMP1 signaling pathway [46]. Our findings of the extensive co-expression of lncRNAs with mRNAs provide a reference for further study of the specific molecular mechanism of atherosclerosis.…”
Section: Discussionsupporting
confidence: 52%
“…Wu et al identified lincRNA-p21 as a therapeutic target in atherosclerosis [45]. Zhan et al found that RP11-714G18.1 may play an atheroprotective role by inhibiting vascular cell migration via the RP11-714G18.1/LRP2BP/MMP1 signaling pathway [46]. Our findings of the extensive co-expression of lncRNAs with mRNAs provide a reference for further study of the specific molecular mechanism of atherosclerosis.…”
Section: Discussionsupporting
confidence: 52%
“…LncRNA BANCR can facilitate vascular smooth muscle cell proliferation and migration through JNK signaling . LncRNA‐RP11‐714G18.1 depresses vascular cell migration through targeting LRP2BP …”
Section: Introductionmentioning
confidence: 99%
“…Many lncRNAs can simultaneously conduct different molecular functions. For example, lncRNA RP11-714G18.1 can inhibit VSMC migration and reduce the adhesion of monocytes to endothelial cells (Zhang et al, 2018). According to Leisegang et al, the lncRNA MANTIS can be strictly regulated by the transcription factors KLF2 and KLF4, which may inhibit ICAM-1-mediated adhesion of monocytes to endothelial cells, thereby slowing the progression of AS (Leisegang et al, 2019).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Myocardial and cerebral infarctions caused by atherosclerotic involvement are often severely debilitating with high mortality rates (Parthasarathy et al, 2010;Kumarswamy et al, 2014). In recent years, long non-coding RNA molecules (lncRNAs) have been found to play a variety of biological functions in the vascular system, such as promoting apoptosis of endothelial cells (Wang J. et al, 2015), inhibiting the migration of vascular smooth muscle cells (VSMCs; Bell et al, 2014;Zhang et al, 2018), and activating apolipoprotein A1 (APOA1)-mediated macrophage cholesterol efflux (Hu et al, 2014;Pan, 2017). There is abundant showing that lncRNAs are involved in all stages of AS plaque formation, regulating key stages of plaque development, such as lipid metabolism, inflammatory cascade reactions, vascular cell proliferation, apoptosis, adhesion and migration, and angiogenesis ( Table 1; Li et al, 2016Li et al, , 2017Aryal and Suárez, 2019).…”
Section: Introductionmentioning
confidence: 99%